Tanggapan Relawan Terhadap Pengalaman Bertugas di Startup Kesehatan Mental - Rahmatullah, Bagas (Rifa'Institute, 2022)
In running the wheel of activity in a company, it is very important for the company to listen to any complaints that are felt by the team, a study found that the feedback or responses provided by the team are very useful for increasing motivation at work. Seeing the urgency of the responses given by the team to the company made researchers interested in learning more through this research in populations on volunteer teams. In this study, researchers used a descriptive approach using a questionnaire containing criticism of existing programs in the division, suggestions for divisional programs, and development suggestions for internal companies with the aim of finding out how volunteers responded while on duty at CV. Sharing Indonesian Stories. There were 8 participants whose data was taken for later analysis. Based on the results of the analysis, there are positive and negative aspects that the company needs to pay attention to so that it can develop better in the future